Challenges and future perspectives of sustainable supplements, functional foods, and nutrigenomics in athletic performance - Naselli, Flores; Cardinale, Paola Sofia; Vasto, Sonya; Proia, Patrizia; Baldassano, Sara; Caradonna, Fabio (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2024)
Nutrition plays a key role in the lives of athletes, sustaining and enhancing sports performance by significantly influencing their performance and general well-being. Functional foods, rich in bioactive compounds and essential nutrients, offer sig-nificant advantages for general health and athletic performance. This review addresses the benefits of sustainable, func-tional foods for health and sporting needs and the strategies to improve sustainability in the food sector. It will explore the connection between sustainable nutrition, nutrigenomics, and sporting needs. Sustainable food offers several advantages over traditional supplements. Thus, it is essential to educate consumers about the environmental impact of conventional sup-plement production and the benefits of sustainable options. The necessary approach must be integrated into food production, distribution, and consumption to meet current nutritional needs. Incorporating sustainability into supplement production and using functional foods to formulate supplements will be explored to point out the advantages of sustainable foods over tradi-tional supplements. This review underscores the importance of public awareness and education in adopting sustainable eating habits, utilizing what nature offers more consciously, and implementing these principles in daily life. The importance of food sustainability is underscored by its impact on climate change and global health, as food production contributes sig-nificantly to greenhouse gas emissions. Addressing this involves improving diet quality while reducing the environmental footprint of food production. Through these efforts, functional foods can serve as a key component in achieving sustainable sports supplementation, benefiting individuals and the planet.
Keywords: nutrition; sport; food sustainability; human health; environmental impact